NAVIGATING TAX COMPLIANCE: THE INTERPLAY OF SELF-ASSESSMENT, SERVICE QUALITY, AND SANCTIONS AMONG INDIVIDUAL TAXPAYERS - Paulus, Hendro (Berkala Akuntansi dan Keuangan Indonesia, 2025)
This study aims to analyze the effect of the self-assessment system, service quality, and tax sanctions on individual taxpayer compliance at KPP Pratama Jakarta Pasar Rebo. A quantitative approach was used by distributing questionnaires to 100 respondents selected through simple random sampling technique. The data were analyzed using the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS) through the SmartPLS Version 4.0 application. The results showed that the self-assessment system and service quality had a positive and significant effect on taxpayer compliance. In contrast, tax sanctions have no significant effect, which indicates the weak implementation of sanctions in the field. This finding supports the Theory of Planned Behavior (TPB) framework, where attitudes, subjective norms, and perceptions of behavioral control are formed more strongly through good systems and services, not through the threat of sanctions alone.